2016
DOI: 10.1063/1.4961916
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of non-perturbative kinetic effects of energetic particles on toroidicity-induced Alfvén eigenmodes in tokamaks and stellarators

Abstract: The resonant interaction of shear Alfvén waves with energetic particles is investigated numerically in tokamak and stellarator geometry using a non-perturbative MHD-kinetic hybrid approach. The focus lies on toroidicity-induced Alfvén eigenmodes (TAEs), which are most easily destabilized by a fast-particle population in fusion plasmas.While the background plasma is treated within the framework of ideal-MHD theory, the drive of the fast particles, as well as Landau damping of the background plasma, is modelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The damping rate weakly depends on the particle density and temperature profiles because the mode width is rather small: it does not change appreciably if we take n e = const or T i = T i (r * ) = const. Artificially setting the mode frequency to values as high as 70 kHz gives the damping rates shown in Table (2). All these magnitudes are in qualitaive agreement with the local estimate above.…”
Section: Damping Of Tae Modes In Wendelstein 7-xsupporting
confidence: 81%
See 1 more Smart Citation
“…The damping rate weakly depends on the particle density and temperature profiles because the mode width is rather small: it does not change appreciably if we take n e = const or T i = T i (r * ) = const. Artificially setting the mode frequency to values as high as 70 kHz gives the damping rates shown in Table (2). All these magnitudes are in qualitaive agreement with the local estimate above.…”
Section: Damping Of Tae Modes In Wendelstein 7-xsupporting
confidence: 81%
“…These mechanisms are Landau damping, continuum damping, radiative damping, and collisional damping. A brief overview of them in stellarators can be found in, e.g., [1], see also a more recent work [2]. The physics of the damping is rather similar in both tokamaks and stellarators.…”
Section: Introductionmentioning
confidence: 97%
“…Refs. [28,34]). Furthermore, the linear mode structure can change in the non-linear phase since it may react to changes of the fast-particle drive [36].…”
Section: Introductionmentioning
confidence: 99%
“…For both co-and cntr-GAEs, increasing beam density results in a modest decrease in mode frequency. This likely reflects changes in the equilibrium, and is supported by work done by Slaby et al which found that the continuum frequencies are decreased in the presence of increased alpha particle pressure 37 . Also apparent in this comparison is that the mode has a different stability threshold in J depending on if J is decreased through n b /n e or v 0 /v A , as the mode can still exist for small J provided that v 0 /v A is sufficiently large.…”
Section: A Equilibrium Effectsmentioning
confidence: 59%
“…Previous work has demonstrated the substantial effects that the beam contribution can have on the equilibrium 29 . Moreover, there is recent work showing that the inclusion of alpha particles can significantly deform the Alfvén continuum 37 . It is important to investigate if these changes in frequency can be attributed to changes in the self-consistent equilibrium or changes in the fast particles driving the mode, independent of the equilibrium.…”
Section: Equilibrium Vs Fast Ion Effectsmentioning
confidence: 99%